2014
DOI: 10.1093/jscr/rju017
|View full text |Cite
|
Sign up to set email alerts
|

Indirect inguinal hernia sac containing testis and spermatic cord in an adult patient with cryptorchidism

Abstract: Sliding hernias are those in which part of the sac wall is formed by a retroperitoneal organ and/or its mesentery protruding outside the abdominal wall cavity. The hernia sac may contain jejunum, ileum, vermiform appendix, Meckel's diverticulum, stomach, ovary, fallopian tube or urinary bladder. Our report features an adult case with cryptorchidism in which testis and spermatic cord constitute a component of the indirect inguinal hernia sac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The hernia was itself being complete with internal ring admitting index finger and sac spreading like cone. Arsalan et al [ 5 ] reported an adult case with cryptorchidism in which testis and spermatic cord constitute a component of the indirect inguinal hernia sac but in the present case testis and spermatic cord were content without any cryptochidism. Spermatocele with testis and cord is to be made extrasacal after incising lateral wall of sac and transfixed at deep ring to prevent recurrence, omentocele or enterocele…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The hernia was itself being complete with internal ring admitting index finger and sac spreading like cone. Arsalan et al [ 5 ] reported an adult case with cryptorchidism in which testis and spermatic cord constitute a component of the indirect inguinal hernia sac but in the present case testis and spermatic cord were content without any cryptochidism. Spermatocele with testis and cord is to be made extrasacal after incising lateral wall of sac and transfixed at deep ring to prevent recurrence, omentocele or enterocele…”
Section: Discussionmentioning
confidence: 47%
“…A patent processus vaginalis and increased cumulative mechanical exposure are risk factors for indirect inguinal hernia occurrence [ 4 ]. Aberrant hernia has been suggested to occur due defective regulatory mechanism of hormones, peptides from the genitofemoral nerve and insufficient release of calcitonin gene-related peptide that have an effect on testicular descent [ 5 ]. In this case, spermatic cord and testis invested by processus vaginalis in embryogenesis failed to disappear altogether after descent.…”
Section: Discussionmentioning
confidence: 99%
“…A patent processus vaginalis and increased cumulative mechanical exposure are risk factors for indirect inguinal hernia occurrence [6]. Aberrant hernia has been suggested to occur due defective regulatory mechanism of hormones, peptides from the genitofemoral nerve and insufficient release of calcitonin gene-related peptide that have an effect on testicular descent [7].…”
Section: Discussionmentioning
confidence: 99%
“…A PubMed search using the terms detailed in Table 1 identified just six previous cases of an ectopic testis between the muscular layers of the abdominal wall, of which two were described in adults. One case reports an indirect hernial sac containing testis and spermatic cord in an adult patient with cryptorchidism 3 while the other reports a 21-year-old patient in whom a testis was identified in the superficial inguinal pouch on ultrasonography of the abdomen, between Scarpa's fascia and the external oblique aponeurosis. 4 Consequently, our case report appears to describe the first case of an ectopic testis between internal and external oblique aponeuroses in an adult.…”
Section: Discussionmentioning
confidence: 99%